"You Little Creep": Evidence of Blatant Dehumanization of Short Groups. Issue 2 (March 2019) - Kunst, Jonas R.; Kteily, Nour; Thomsen, Lotte
Physical cues influence social judgments of others. For example, shorter individuals are evaluated less positively than taller individuals. Here, we demonstrate that height also impacts one of the most consequential intergroup judgments—attributions of humanity—and explore whether this effect is modulated by the tendency to value hierarchy maintenance. In Study 1, the shorter participants perceived a range of out-groups to be, the more they dehumanized them, and this tended to be particularly pronounced among those scoring high on social dominance orientation (SDO). In Study 2, participants dehumanized an out-group more when they were led to believe that it was relatively short. Finally, Study 3 applied a reverse correlation approach, demonstrating that participants in general, and especially those scoring high on SDO, represented shorter groups in ways less consistent with full humanity than they represented taller groups. Together, this research demonstrates that basic physical height cues shape the perceived humanity of out-groups.